Potencial de compostos fenólicos como antimicrobianos e/ou moduladores da resistência em Staphylococcus aureus - Silva, Helena Taina Diniz (2015)
Phenolic compounds are a major class of plant secondary metabolites synthesized for plant and adaptation to environmental stress defense. Are divided into three groups: phenolic acids, flavonoids and tannins. Have been proposed as having a variety of biological effects on human health and microorganisms such as S. aureus. Cases of infections caused by strains of S. aureus multi drug resistant (MDR) has increased over the years. Among the strategies to combat resistance of S. aureus to antibiotics, is the discovery of so-called modifiers resistance (Resistance-Modifying Agents - RMA). In this study, we evaluated the potential modulator and synergistic effect of flavonoids, tannins and phenolic acid on antibiotic activity norfloxanina (NOR), tetracycline (TET) and erythromycin (ERI) in strains of S. aureus. Six flavonoids have been tested - O-glycoside and C-glycoside - and their aglycone derivatives, two tannins (gallotannin and ellagitannin), phenolic acids (hydroxydiphenic acid and cinnamic acid derivatives). The compounds tested showed no antimicrobial activity at 128 μg/mL (MIC between 256 and 512 μg/mL). In the modulation test, the O-glycosylated flavonoids showed no reducing effect of the MIC of antibiotics tested, however, its aglycone derivatives reduced the MIC in the NOR sixteen fold (8 to 128 μg/mL), in contrast, the Cglycosylated flavonoids, quercetin and myricetin, reduced the MIC in the NOR up to four fold (32 to 128 μg/mL) and their aglycone derivatives showed no reducing effect MIC of the tested antibiotics; the hexahydroxydiphenic acid (gallic acid) showed no reducing effect of MIC of the tested antibiotics; among the cinnamic acid derivatives tested, only 3-methoxycinnamic acid, 3,4-dimethoxycinnamic acid and 3,4,5-trimethoxycinnamic acid reduced the MIC in the NOR (64 to 128 μg/mL), while the 3-methoxycinnamic acid presented reducing effect of tetracycline MIC (64 to 32 μg/mL); the ellagitannin (ellagic acid) showed no reducing effect of MIC of antibiotics tested, already the gallotannin (tannic acid - TA) reduced thirty-two fold the MIC NOR (128 to 4 μg/mL), the test checkerboard TA had effect synergistic when applied in combination with NOR (FICI = 0.15) TA MIC decreased from 512 to 64 μg/mL (eight fold) while the MIC of NOR decreased from 128 to 4 μg/mL (thirty-two fold). The results demonstrate that the phenolic compounds have a potential application as an adjunct to antibiotics, particularly when in combination with NOR.